Intracerebral Abscess: A Complication of Severe Cystic Fibrosis Lung Disease - Mark E Fenton; Donald W Cockcroft; John A Gjevre (Canadian Respiratory Journal)
Intracerebral abscess is an uncommon complication of severe cystic fibrosis lung disease. The present report describes a case of fatal multiple intracerebral abscesses in a patient with a severely bronchiectatic, nonfunctioning right lung and chronic low-grade infection. The patient was previously turned down for pneumonectomy. Intracerebral abscess in cystic fibrosis and the potential role of pneumonectomy in the present patient are discussed.